2016
DOI: 10.1680/jstbu.15.00046
|View full text |Cite
|
Sign up to set email alerts
|

Load transfer and arching analysis in reinforced embankment

Abstract: In a previous study, a series of 9 model tests performed on embankment models resting on soft clay treated with and without ordinary stone columns (OSC), encased stone columns (ESC), and with horizontal layer of geogrid at interface and at 0·1 h height has been carried out to investigate the behaviour of piled (stone columned) and geogrid reinforced embankments. In this paper, these tests are simulated numerically by the finite element method using the program Geostudio (SIGMA/W). Firstly, reanalysis was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The correlation between the influencing factors and the vertical stress-settlement response of the underground soil pile-embankment system was established through parameter research [12] . Through the numerical simulation of the embankment model [13] , it was found that the bearing capacity increased by 13% and 23% respectively when the geogrid layer was embedded at the interface and 0-1h. For soft soil embankments reinforced with ordinary stone pillars, as the load increases, the settlement value will decrease, which means the ultimate bearing capacity increases [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the influencing factors and the vertical stress-settlement response of the underground soil pile-embankment system was established through parameter research [12] . Through the numerical simulation of the embankment model [13] , it was found that the bearing capacity increased by 13% and 23% respectively when the geogrid layer was embedded at the interface and 0-1h. For soft soil embankments reinforced with ordinary stone pillars, as the load increases, the settlement value will decrease, which means the ultimate bearing capacity increases [14] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, according to Elias et al (2001), the advantages provided by using geosynthetic materials to reinforce soil structures are noted under these conditions. Besides, the polymeric material can be employed with other solutions to improve lateral support, such as exposed by Fattah et al (2015Fattah et al ( , 2016a. Many deterministic methods have been proposed aiming to determine the key design features of geosyntheticreinforced soil structures (Koerner, 2012;Ariyarathne and Liyanapathirana, 2015;Fonseca and Palmeira, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major uncertainties in the design is the interaction between underground structure and surrounding soils which is dependent on the type and shape of structure, type of surrounding soils and free field stresses. Arching mechanisms play a pivotal role in the interaction between surrounding soils and underground structures/inclusions (e.g., Lee et al 2006;Meguid et al 2008;Costa et al 2009;Van Eekelen 2015& Fattah et al 2016. Depending upon the relative displacement between the underground structure/inclusion and adjacent soils, redistribution of stresses would occur as a result of the formation of either active or passive arching.…”
Section: Introductionmentioning
confidence: 99%